PENGEMBANGAN PRODUK OLAHAN BERBAHAN DASAR SEMANGKA BERBASIS EKONOMI KREATIF DI DESA GAPURA, LOMBOK TENGAH - Jufri, Akhmad; Bayuaji, Datu Garindra Adlahaq; falah, Epha khoiriya; Wirawan, Lalu Hendra; qurtubi, Muhammad nazri; Amnur, Fitrah Putra; Farhira, Farras Julfa; Mukhoyyaroh, Uswatun; Laksmi , Ni Nyoman Sita; Puspita, Rofita; Rosiani, Rani; Fitriani, Hijjatul (Jurnal Wicara, 2024)
Community Service (KKN) is a form of community service activity carried out by universities. In the KKN activities carried out in Gapura Village, located in Pujut District, Central Lombok Regency, West Nusa Tenggara Province, various activities were carried out with the main target of mentoring watermelon-based processing as a basis for the creative economy. The purpose of implementing this KKN activity is to maximize the use of local resources through innovation and development of agricultural-based processed products, with the main focus on the management of watermelon agricultural products in Gapura Village, Central Lombok. The results of this activity are the development of watermelon-based processed products in Gapura Village, Central Lombok, aimed at maximizing the use of agricultural products, especially in overcoming the abundant production of watermelon, most of which has not been utilized effectively, especially the skin which is often considered waste. With this background, this study aims to develop watermelon processed products, including watermelon chips innovations from the skin, as an effort to present creative and economical solutions. Through the method of mentoring activities for local residents, especially mothers as KKN activities, continued with the processing process, this study also includes training and mentoring programs for the community regarding effective processing and packaging techniques. As a result, the comprehensive utilization of watermelon has not only succeeded in reducing waste, but also increasing economic value for the people of Gapura Village. In addition, watermelon rind chips products show significant market potential, thanks to their uniqueness and contribution to the principle of sustainability. Therefore, this watermelon-based processed product development initiative offers a sustainable creative economic model that has the potential to improve the welfare of farmers in Gapura Village.